STUDI TENTANG PENERAPAN CITY BRANDING MAGNIFICENT SAMARINDA OLEH DINAS KOMUNIKASI DAN INFORMATIKA - Zulfi Sandy Kurniawan (Bajang Institute, 2022)
This study aims to determine the City Branding Magnificent Samarinda is known by the wider community. This type of research is qualitative. Sources of research data are key informants and informants. Data collecting techniques in research are in the form of observation, interview, documentation, and literature study. The data analysis technique used was data reduction, data presentation, and conclusion drawing. The results of this study show that 6 aspects of City Branding, namely Presence, place, pre-requisites, pople, pulse, and potential have their respective advantages in increasing the application of Branding Magnificent Samarinda. Maintain the existing system so as not to become a deviation, develop business actors, preserve potential natural resources provide education to the public about City Branding, and create events. In addition, City Branding that is being implemented in Samarinda City has inhibiting and supporting factors. Supporting factors can be in the form of gaining support from the Central Government, holding events both within the City and outside the City, while the inhibiting factor in conducting Magnificent City Branding Samarinda is the absence of Investors who invest in Kota Samarinda, there is no community concern in running promotions consistently.